Tracing transnationalism and neocolonialism in Zia Haider Rahman’s in The Light of What We Know - Mayen, Tasmia (BRAC University, 2016)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2015.